Effect of Mining Thickness on Overburden Movement and Underground Pressure Characteristics for Extrathick Coal Seam by Sublevel Caving with High Bottom Cutting Height - Yongkang Yang; Yanrong Ma; Chunxu Ji; Tianhe Kang; Xingyun Guo (Advances in Civil Engineering)
Because the coal seam is particularly thick and the mining intensity is large, the mining of extremely thick coal seams often causes a wide range of disturbed fractures, which in turn induces the phenomenon of strong underground pressure such as induced support crushing and water inrush. Through theoretical analysis, laboratory similarity simulation test, and other methods, this paper studies the effect of mining thickness on overburden movement and underground pressure characteristics for extremely thick coal seams by sublevel caving with high bottom cutting height. Some conclusions can be drawn as follows: (i) under the “beam-hinged cantilever beam rocks” structure theory, the rock pillar thickness which needs to be controlled increases linearly as a function of mining thickness is achieved, and the reason of increased of support resistance in full-mechanized caving mining in extremely thick seams is explained in the theory; (ii) based on the results of the theoretical analysis and the lab simulation tests, the law of the abutment pressure peak is inverse to the full-seam mining thickness, and the distance between abutment peak and working face is proportional to the full-seam mining thickness, that is to say that the damage range of overlying strata increased; (iii) there are three working states of loading support in extrathick coal seams, such as normal circumstance, lower main roof pressure, and higher main roof pressure, meanwhile these states keep changing; (iv) under the guarantee of stope safety conditions, due to lower support strength, it will benefit the special thick seam top-coal caving under normal circumstance; (v) increasing the supporting strength can balance the impact loading under the lower main roof pressure, guaranteeing valid support for roof strata; (vi) by releasing high pressure, due to lower production, lower recovery rate of coal and other measures guarantee the stability of the stope support in the case of the higher main roof pressure.